What means ‘orient oneself in thinking’ within the catholicism? Among the bible, tradition or dogma assumed in a fundamentalist sense - Caviglia Marconi, Alessandro (2012)
This work seeks to answer the question whether it is possible that there are fundamentalist positions within the Catholicism. For this, the author begins by clarifying the term “fundamentalist” in its original context, which is the evangelical fundamentalism in the United States at the beginning of the twentieth century. Following, important distinctions as “conservatism” and “fundamentalism” are performed. It defines what characterizes the fundamentalism, namely “the exclusive intratextual reference” in order to see the three possible forms of it in the Catholicism: the first is focused on the tradition, the second on the dogma and the third (which is very rare in the Catholicism) on the biblical text. This article is focused on its analysis of the first two forms of fundamentalism. In the third part of the work, the Catholicism´s beginning of a possible confinement in fundamentalist forms is presented, thanks to its connection with modernity and, in particular, with the illustration.